2019
DOI: 10.1111/1365-2745.13195
|View full text |Cite
|
Sign up to set email alerts
|

Droughts and the ecological future of tropical savanna vegetation

Abstract: Climate change is expected to lead to more frequent, intense and longer droughts in the future, with major implications for ecosystem processes and human livelihoods. The impacts of such droughts are already evident, with vegetation dieback reported from a range of ecosystems, including savannas, in recent years. Most of our insights into the mechanisms governing vegetation drought responses have come from forests and temperate grasslands, while responses of savannas have received less attention. Because the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 188 publications
2
64
0
1
Order By: Relevance
“…In this study, a continuous drying period was found from 2000 to 2008, and then the drought trend eased in 2009 ( Figure 2); however, the WUE was still very low in 2009 and 2010. This low WUE was due to the drought legacy effect that was found in a large body of previous studies, which reported that the effects of drought on ecosystem WUE exhibit a legacy effect [6,24,56]. However, most of these studies compared the relationship between WUE and drought in the previous year.…”
Section: Serious Drought Will Lead To the Drought Legacy Effectmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, a continuous drying period was found from 2000 to 2008, and then the drought trend eased in 2009 ( Figure 2); however, the WUE was still very low in 2009 and 2010. This low WUE was due to the drought legacy effect that was found in a large body of previous studies, which reported that the effects of drought on ecosystem WUE exhibit a legacy effect [6,24,56]. However, most of these studies compared the relationship between WUE and drought in the previous year.…”
Section: Serious Drought Will Lead To the Drought Legacy Effectmentioning
confidence: 96%
“…This finding indicates that the WUE was affected by the drought in the previous one and two years in most vegetation areas during the drought periods. Previous studies suggested that arid plants respond to a moisture restriction environment by reducing aboveground biomass or even hibernating in consecutive dry years, and the biomass increases rapidly when the moisture is sufficient [56]; however, serious declines in soil moisture cause successive years of drought, and one year of recovery is not sufficient to provide the moisture to meet the basic physiological needs for vegetation growth. This phenomenon may explain the fact that the WUE was still very low in 2009 and 2010, although the drought ended in 2008.…”
Section: Serious Drought Will Lead To the Drought Legacy Effectmentioning
confidence: 99%
“…Plants exhibit different strategies in the face of dry conditions. For example, anisohydric species are at risk of hydraulic failure as a result of xylem cavitation while isohydric species regulate stomata and thereby maintain plant water potentials to avoid cavitation, but are at risk of carbon starvation from depletion of carbohydrate reserves (Sala et al 2012, Klein 2014, Sankaran 2019). Here, we focused on periods where annual rainfall was lower than its annual average and not specifically on drought.…”
Section: Below-surface Water Control On Interannual Gppmentioning
confidence: 99%
“…Empirical data and model projections suggest that regional‐scale droughts are increasing in frequency, duration, and magnitude across the globe (Dai , Trenberth , Cook et al ). These more severe and prolonged droughts have the potential for large and long‐lasting effects on ecosystem structure and function (Du et al , Sankaran and Staver ). To maintain function in response to extreme drought, ecosystems must exhibit either high resistance during drought (e.g .…”
Section: Introductionmentioning
confidence: 99%